CD95(APO-1/Fas)-Mediated apoptosis: live and let die - Krammer, Peter H. (Advances in immunology, 2008)
In the present time there is a true bull market for apoptosis as it has almost become a household word. Even nonspecialists know that fingers and toes do not simply grow out of the embryonic hand or foot-adage but develop out of the limb buds by also involving the death of cells—apoptosis—in the interdigital spaces. It is now known that apoptosis is involved in many physiological processes, and there is hardly any disease whose pathogenesis can be explained without apoptosis. Thus, programmed cell death or apoptosis is an integral part of life. In addition, apoptosis is essential for the deletion of autoreactive T cells in the thymus. This mechanism is the basis of central self-tolerance. In lymph nodes and the spleen, apoptosis causes deletion in the T and B cells. Peripheral deletion by apoptosis is a second line where the immune system establishes self-tolerance and where it downregulates an excessive immune response. Data show that the CD95/CD95L system contributes substantially to the elimination of peripheral lymphocytes. To investigate the role of CD95/CD95L in TCR-mediated apoptosis, malignant Jurkat T cells as a model are triggered via the TCR in the presence of blocking anti-CD95 antibodies. These reagents prevented anti-CD3-induced apoptosis.
Available online 1 March 2008
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 03.03.2021